2021
DOI: 10.1177/26320770211051965
|View full text |Cite
|
Sign up to set email alerts
|

What do Support Professionals do in Schools? Construction and Validation of an Instrument for Assessing Whole-School Prevention and Promotion Strategies

Abstract: Education policies worldwide have encouraged the entry and permanence of nonteaching support professionals in schools. During the last decade, Chilean regulations have allowed a massive incorporation of these professionals—mostly school psychologists and social workers—in publicly funded schools. However, there is scarce evidence regarding the actions of these professionals, including whether and how they align with whole-school approaches. In this study, we constructed and validated scales to assess professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In Latin America, Chilean data has demonstrated that the management of school violence is not a priority and that efforts to tackle it are focused on the fulfillment of administrative obligations rather than on improving processes. According to Ascorra et al (2021) , this situation is related to the imbalance of the educational system, in which different school districts, especially public ones, have to respond to homogeneous standards from dissimilar base conditions, being forced to respond under bureaucratic accountability and with educational processes centered on high-stakes testing ( López et al, 2021a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…In Latin America, Chilean data has demonstrated that the management of school violence is not a priority and that efforts to tackle it are focused on the fulfillment of administrative obligations rather than on improving processes. According to Ascorra et al (2021) , this situation is related to the imbalance of the educational system, in which different school districts, especially public ones, have to respond to homogeneous standards from dissimilar base conditions, being forced to respond under bureaucratic accountability and with educational processes centered on high-stakes testing ( López et al, 2021a , b ).…”
Section: Introductionmentioning
confidence: 99%